2016
DOI: 10.1515/jgth-2015-0038
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tori of free group automorphisms, and the Bieri–Neumann–Strebel invariant of graphs of groups

Abstract: Abstract. Let G be the mapping torus of a polynomially growing automorphism of a finitely generated free group. We determine which epimorphisms from G to Z have finitely generated kernel, and we compute the rank of the kernel. We thus describe all possible ways of expressing G as the mapping torus of a free group automorphism. This is similar to the case for 3-manifold groups, and different from the case of mapping tori of exponentially growing free group automorphisms. The proof uses a hierarchical decomposit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Hence we get as special cases P L 2 (G; p 0 ) = P A (G) by Theorem 3.2 (3) and this polytope determines the Alexander norm, and on the other hand P L 2 (G; p ∞ ) = P L 2 (G) which determines the Thurston norm. Theorems 6.2 and 6.3 both rely on the following lemma which follows from the train track theory of Bestvina-Feighn-Handel [BFH]; see [CL,Proposition 5.9] for the argument. Lemma 6.7.…”
Section: Upg Automorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence we get as special cases P L 2 (G; p 0 ) = P A (G) by Theorem 3.2 (3) and this polytope determines the Alexander norm, and on the other hand P L 2 (G; p ∞ ) = P L 2 (G) which determines the Thurston norm. Theorems 6.2 and 6.3 both rely on the following lemma which follows from the train track theory of Bestvina-Feighn-Handel [BFH]; see [CL,Proposition 5.9] for the argument. Lemma 6.7.…”
Section: Upg Automorphismsmentioning
confidence: 99%
“…By [CL,Remark 5.6], we have b 1 (G) 2 and similarly for G 1 and G 2 . Hence by Theorem 3.2 (2) and (3) as well as the above matrix decomposition, we compute in Wh w (Γ k ) ρ (2) u (G; p k ) = −[p k (I − t · F (g))] + [p k (t − 1)] = −[p k (I − t · F (g 1 ))] − [p k (I − t · F (g 2 ))] + [p k (t − 1)] = (j 1 ) * (ρ (2) u (G 1 ; p 1 k ))) + (j 2 ) * (ρ (2) u (G 2 ; p 2 k ))) − [p k (t − 1)] (6.2)…”
Section: Upg Automorphismsmentioning
confidence: 99%
“…For this, we note that the corresponding tubular group G p,q will have such a finite index subgroup H too, by [6] Proposition 4.3 (iii). Now H will also be a tubular group, but [11] Corollary 2.10 states that a tubular group has a symmetric BNS invariant and so cannot be a strictly ascending HNN extension of any finitely generated group.…”
Section: Corollarymentioning
confidence: 99%
“…In a recent paper [CL,Theorem 5.2] Cashen and Levitt computed Σ(G) for the case where G is the mapping torus of a polynomially growing automorphism φ of F N . They showed that in that situation Σ(G) is centrally symmetric and consists of the complement of finitely many rationally defined hyperplanes in H 1 (G, R).…”
Section: Foliations and Flowsmentioning
confidence: 99%